Spirituality and Creativity in Coping, Their Association and Transformative Effect: A Qualitative Enquiry - Corry, Dagmar Anna S. (Religions, 2015)
While the beneficial effects on mental health of spirituality and creativity as separate entities have been well documented, little attention has been given to the interactive effect of the two constructs in coping. Recently, the theory of transformative coping and associated Transformative Coping Model have been developed and examined from both theoretical and quantitative perspectives. To extend this work, the present study critically examined the theory of transformative coping and associated Transformative Coping Model from a qualitative perspective. Ten interviews were conducted among Northern Irish and Irish artists, contemplative prayer group members, and mental health service users. Data were analysed using Interpretative Phenomenological Analysis. The results showed that the majority of participants had experienced stress and trauma, and have suffered mental ill-health as a consequence. Most defined themselves as both creative and spiritual, and resorted to a spiritual attitude along with creative expression in order to cope with traumatic events and ongoing stressful situations. Most participants believed that their creativity was rooted in their spirituality and that the application of both helped them to transform negative emotional states into positive ones. This, in turn, gave them increased resilience to and a different perspective of stressful events, which aided and improved their coping skills throughout the lifespan.